ANALYSIS OF STUDENTS' CREATIVE THINKING IN SOLVING PROBLEMS OPPORTUNITIES BASED ON STUDENTS' LEARNING - Nazilatun Ni'mah; Ali Shodikin (Hipotenusa Journal of Research Mathematics Education (HJRME), 2022)
The purpose of this research is research in creative thinking on student learning with opportunity material. The research method used is a qualitative research method, tajing the subject of class VIII junior high school students in 2021/2022. Based on the results of the discussion on creative thinking skills, students are given to obtain information on creative thinking skills on the opportunity material that has been taught.